Pharmacogenetic relevance of CYP4F2 V433M polymorphism on acenocoumarol therapy - Pérez-Andreu, Virginia; Roldán, Vanessa; Antón, Ana Isabel; García-Barberá, Nuria; Corral, Javier; Vicente, Vicente; González-Conejero, Rocio (Blood, 2009)
VKORC1 and CYP2C9 polymorphisms are used to predict the safe dose of oral anticoagulant therapy. A new variant of CYP4F2 (V433M) has recently been related to the required warfarin dose. We evaluated its influence in earliest response to acenocoumarol in 100 selected men who started anticoagulation (3 mg for 3 consecutive days). V433M genotype exerted a gene dosage-dependent effect on the decrease of factors II, VII, IX, and X in the earliest response to acenocoumarol, with homozygous 433V subjects being the most sensitive. Similarly, after the initiation of therapy, international normalized ratio also experienced a gene dosage-dependent effect (P = .015), and 433V subjects needed 4 mg/week less than 433M carriers to achieve a steady anticoagulation (P = .043). Multivariate linear regression analysis revealed a significant contribution of V433M polymorphism to variability of both early international normalized ratio value (R2 = 0.14) and dose requirements (R2 = 0.19). Our data underline the relevant role of CYP4F2 V433M polymorphism in the pharmacogenetics of coumarin anticoagulants.